MEKANISME PEMBENTUKAN PERATURAN DAERAH DAN IMPLIKASI DIBATALKANNYA PERATURAN DAERAH BAGI PROGRAM LEGISLASI DAERAH PROVINSI DAN KABUPATEN/KOTA - Rakhmat Nopliardy (Al-Adl : Jurnal Hukum, 2017)
AbstractConstitutionally, Article 18 Paragraph (6) of the 1945 Constitution of the State of the Republic of Indonesia states that "Local government has the right to enact regional regulations and other regulations to implement autonomy and assistance tasks". Regional regulation as intended is prohibited against the public interest and / or higher legislation ". If these signs are violated then the local regulation may be canceled or requested to be canceled. In 2015, there aren't local regulation is canceled for South Kalimantan Province or for Tabalong Regency. However, several years earlier in Tabalong Regency there were several local regulations that were canceled, namely Local Regulation No. 15 of 2004 concerning Trade Business License and Regional Regulation No. 16 of 2004 concerning Company Registration Certificate.Keyword : Regional Regulation, Decentralitation, Legislation Regional Program